2021
DOI: 10.1007/s40429-021-00368-6
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Opioid Overdose Risk Factors

Abstract: Purpose of Review The purpose of this review is to provide a review of the current literature surrounding opioid overdose risk factors, focusing on relatively new factors in the opioid crisis. Recent Findings Both a market supply driving force and a subpopulation of people who use opioids actively seeking out fentanyl are contributing to its recent proliferation in the opioid market. Harm reduction techniques such as fentanyl testing strips, naloxone education and distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
11

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 97 publications
2
5
0
11
Order By: Relevance
“…The only statistically significant changes in toxicology between 2019 and 2020 were decreases in use of heroin and alprazolam. The decrease in heroin in Tennessee is in accordance with other jurisdictions [ 7 , [31] , [32] , [33] ]. Some studies have reported decreasing benzodiazepine use as well [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…The only statistically significant changes in toxicology between 2019 and 2020 were decreases in use of heroin and alprazolam. The decrease in heroin in Tennessee is in accordance with other jurisdictions [ 7 , [31] , [32] , [33] ]. Some studies have reported decreasing benzodiazepine use as well [ 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, heroin in any combination was only detected in 5.6% of testing results. Taken together, these results help to describe the local drug landscape, which consists predominantly of fentanyl, and most often with no additional illicit adulterants, and a dwindling presence of heroin (36,37). On a more participant-centric level, using DCS with FTS to inform participants about the presence of fentanyl in their submitted specimen has been shown to be an effective risk mitigating strategy as demonstrated in previous studies (15,16,30,31,38).…”
Section: Discussionsupporting
confidence: 59%
“…In this vein, our results indicated that over half (52.9%) of the participants reported their specimens as heroin and, more importantly, 16.6% reported fentanyl alone or in combination with heroin or cocaine. Perhaps participants testing specimens that they believed to be fentanyl re ects an increase in opioid tolerance and dependence that is di cult to satisfy with heroin alone, leading to fentanyl seeking behaviors in drug use (36,37,39,40). Another possibility is that those reporting specimens as heroin, might have been using the term as a catch all reference to opioids, including fentanyl, as has been previously reported (41).…”
Section: Discussionmentioning
confidence: 96%
“…Esta substância é 50-100 vezes mais potente que a morfina, podendo levar a overdose com doses muito pequenas. Como dito, a pandemia levou a um isolamento social, fazendo com que mais pessoas utilizassem drogas sozinhas, fator que aumenta a letalidade das overdoses, uma vez que não é possível a chamada de socorro (FOGLIA et al, 2021).…”
Section: Resultsunclassified